2021
DOI: 10.1371/journal.pbio.3001143
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell longitudinal analysis of SARS-CoV-2 infection in human airway epithelium identifies target cells, alterations in gene expression, and cell state changes

Abstract: There are currently limited Food and Drug Administration (FDA)-approved drugs and vaccines for the treatment or prevention of Coronavirus Disease 2019 (COVID-19). Enhanced understanding of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and pathogenesis is critical for the development of therapeutics. To provide insight into viral replication, cell tropism, and host–viral interactions of SARS-CoV-2, we performed single-cell (sc) RNA sequencing (RNA-seq) of experimentally infected human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
231
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(276 citation statements)
references
References 83 publications
41
231
2
2
Order By: Relevance
“…SARS-CoV-2 (USA-WA1/2020; BEI Resources) was generously provided by the Wilen laboratory (Yale University, New Haven, CT). Virus was cultured on Vero E6 cells, a filtered supernatant was used as the virus stock, and titer was determined by plaque assay as described previously ( Ravindra et al, 2021 ). We confirmed that the cell lysate/supernatant did not contain significant levels of IFN or other molecules that activate ISG expression by mock-inoculating BEAS2B cells with UV-inactivated stocks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 (USA-WA1/2020; BEI Resources) was generously provided by the Wilen laboratory (Yale University, New Haven, CT). Virus was cultured on Vero E6 cells, a filtered supernatant was used as the virus stock, and titer was determined by plaque assay as described previously ( Ravindra et al, 2021 ). We confirmed that the cell lysate/supernatant did not contain significant levels of IFN or other molecules that activate ISG expression by mock-inoculating BEAS2B cells with UV-inactivated stocks.…”
Section: Methodsmentioning
confidence: 99%
“…Innate immune responses such as the antiviral IFN response are often critical for curtailing early viral replication at mucosal surfaces; however, recent work shows that SARS-CoV-2 antagonizes and delays this response ( Banerjee et al, 2020b ; Blanco-Melo et al, 2020 ; Konno et al, 2020 ; Xia et al, 2020 ; Zhou et al, 2020 ; Martin-Sancho et al, 2021 ; Ravindra et al, 2021 ). Nonetheless, there is strong evidence that the IFN response protects against severe COVID-19, from both genetic and autoantibody studies, and from in vitro studies showing protection of cells using recombinant IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…Two single cell sequencing data sets representing infected and non-infected cells directly derived from human samples 31 and cultured human bronchial epithelial cells 32 (HBECs) were used to identify the areas of the COVID-19 PHARMACOME responding at gene expression level to SARS-CoV-2 infection. Details of the gene expression data processing and mapping are available in the supplementary material (see section “Gene expression data analysis”).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to gas exchange, the human airway epithelium has been recognized to function as the main entry point for several pathogens. Notably, human airway epithelial cells represent a primary target of coronaviruses, including the highly transmissible and pathogenic Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) [ 4 , 5 , 6 ]. To defend itself from pathogens such as SARS-CoV-2, epithelial cells have adapted numerous strategies that include tightly packed epithelial cells forming tight junctions, mucosal epithelium trapping invading pathogens in the secreted mucus barrier and the expression of pattern-recognition receptors.…”
Section: Introductionmentioning
confidence: 99%